"Thumb Exercise": An Interpretative Phenomenological Analysis of Psychosocial Factors Encouraging Inactive Adults to Engage with Their Smartphones Rather than Physical Activity. Issue 1 (9th April 2020) - Hedges, Tallulah Sara; Garip, Gulcan
Background: Physical inactivity accounts for up to 1.6 million deaths each year. With UK adults spending approximately eleven times longer using their smartphones than exercising, research suggests that frequent smartphone use is linked to poor physical fitness. Previous research on the psychosocial influences of both problem smartphone use, and physical activity barriers and facilitators exist, however insight into the psychosocial underpinnings of why inactive individuals choose to engage with their smartphones rather than physical activity is understudied. Aims: This study provides a qualitative exploration of the psychosocial factors that encourage inactive adults to engage with their smartphones rather than physical activity. Methods: Thirteen (female = 10) participants aged between 18 and 39 completed an online qualitative survey. The subjective experiences and perceptions from participants' survey responses were analysed using interpretative phenomenological analysis, with a phenomenological epistemological approach. Results: Three themes were identified: the first theme identified that the psychosocial influence of smartphone engagement was to escape unpleasant realities; the second theme depicts that the psychosocial barrier of physical activity engagement was perceptions in relation to the financial and task-oriented costs that physical activity incurs; the third theme captured that social support necessities are being fulfilled through smartphone communication, therefore as a counterpart, physical activity is deemed to be a desolate operation. Conclusions: The findings from this study provide recommendations that harness social support and smartphone capabilities for motivating inactive adults to maintain physically active lifestyles.